Effect of Vertebral Fracture on Quality of Life - Figen Yılmaz; Füsun Şahin; Ayla Çağlıyan; Şule Taşpınar; Beril Özcan; Banu Kuran (Galenos Yayinevi, 2005)
Objective: The aim of this study was to investigate the effect of vertebral fractures on quality of life in postmenopausal women. Method: 41 postmenopausal women were classified into two groups as those having osteopenia (Group I t score>-2.5) or osteoporosis (Group II t score£-2.5). Patients were further investigated by lateral spine radiographs with respect to vertebral fracture defined as 20 percent height loss compared to the neighbouring vertebra. Short Form-36 (SF-36), Quality of Life Questionnaire of the European Foundation for Osteoporosis (QUALEFFO) and Notthingam Health Profile (NHP) were the questionnaires used to evaluate life quality. Results: The mean age of the 11 patients in Group I was significantly (p£0.05) greater than those in Group II. Age at menopause, height and weight were not significantly different between the groups. 16 patients had vertebral fractures and the number of fractures was 25. Energy subgroup of SF-36 was significantly lower in Group II than in Group I (37.3±16 vs 48.2±11, p£0.05). Only physical activity subgoup of the NHP was significantly different between the two groups. On the other hand, there was not any significant difference between the two groups and between the patients with and without vertebral fractures with respect to life quality. Number of fractures was significantly correlated (r= 0.31) with the home activities subgoup of QUALEFFO 41 and physical activity subgroup of NHP (r= 0.32). Conclusion: Life quality indicis of osteoporotic patients were almost identical to osteopenic patients which suggested that osteoporosis is not a life quality diminishing disease in patients in the 6th decade. The indicis could not also disemminate patients with and without vertebral fractures either.